Family-based NGS panel testing of cardiopathies and arrhythmic syndromes - Hrazderova, Hana; Petrkova, Jana; Crhova, Anna; Herkommerova, Klara; Mahutova, Kvetoslava; Nejezchlebova, Julie; Petrkova, Lenka; Boucek, Lubos; Boday, Arpad; Tavandzis, Spiros (Frontiers in Genetics, 2025)
Hereditary forms of cardiovascular disease represent a highly heterogeneous group of disorders with a prevailing autosomal dominant inheritance pattern, incomplete penetrance, and variable expressivity. Segregation analysis can help elucidate the genetic aetiology of these diseases, which may be ambiguous within individual families, thereby allowing for a more accurate risk assessment of family members. In this study, we present an alternative approach to co-segregation studies based on comprehensive clinical and molecular genetic diagnostics as part of routine testing. Next-generation sequencing was performed in 58 individuals from 12 families, including asymptomatic individuals. Pathogenic sequence variants and variants of uncertain significance of genes related to cardiopathies and arrhythmic syndromes were identified in 7 families, and their segregation within these families was observed. All willing family members were tested extensively from the start of the diagnostic process, as opposed to testing only genes found in the proband. This method enabled faster risk stratification and clinical follow-up of at-risk family members, facilitating improved disease prevention and personalised patient management.